The Wiley international handbook on psychopathic disorders and the law diagnosis and treatment - Felthous, Alan R.; Sass, Henning (John Wiley & Sons, Ltd., 2021)
"In 2008 we were delighted to have been honored with the Manfred Guttmacher Award by the American Psychiatric Association and the American Academy of Psychiatry and the Law for the best recent publication in forensic psychiatry. For this honor we are in debt to our outstanding contributors to the First Edition of the International Handbook on Psychopathic Disorders and the Law. The Preface to Volume I, First Edition, remains as an essential introduction to Volume I, Second Edition and so is not iterated here"--